Monograph on substance abuse and its related studies in the Caribbean ([CCS] [Georgetown]GY, 2008)
Presents bibliographical references covering areas of research in the field of substance abuse and related studies in the Caribbean during the period 1990-2007.
Compiled during the period September 2007 to April 2008